Social housing in Algeria: case study of Batna city - Djafri, Riadh; Mohamed Osman, Mariana; Rabe, Noor Suzilawati; Shuid, Syafiee (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The housing crisis has become a major concern among Algerian citizens seeking a decent life. Low- and medium-income Algerians are facing this issue, despite various policies introduced by the state to ensure everyone is having access to housing provision. Based on the literature, majority of low- and medium-income Algerians are unable to own or buy a decent house, this leads them renting low-quality houses. The article aims to describe the current housing policies and the various housing programmes implemented in Algeria. An analysis on the architectural design of a sample of social housing units will also be discussed in this article. The findings of this research highlight the deficits, and the inferior quality of social housing in Batna city as a particular case study. Therefore, the collaboration of different stakeholders including government policies, architects and designers are needed for good quality social housing development.